HUMAN RIGHTS ISSUES AS THE BASIS OF MODERN-CONTEMPORARY THINKING IN ISLAM - Idham Halid, Ahmad Ridhoni; Kamal, Akhmad; Ridha, M. Farid; Sahana, Rihan Faza (SERUMPUN : Journal of Education, Politic, and Social Humaniora, 2023)
Modern-contemporary-based scientific studies that give birth to answers to actual problems in the progress of the times are getting a lot of attention by academics and the government at this time. One of the most discussed issues is related to human rights. As a natural right that is owned by every human being on earth, of course it raises a variety of different views, such as the different views held by the West and Islam. The existence of these differences also has a major influence on the understanding of human rights and their application in life. It is undeniable that many Muslims are influenced by Western human rights doctrines so that they are applied in everyday life. To overcome this threat, Muslim scholars try to provide ideas that are relevant to modern-contemporary times that originate from the teachings of Islam.